1993
DOI: 10.1038/ng0293-151
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of variable exon 9 skipping in cystic fibrosis transmembrane conductance regulator mRNA

Abstract: Variable in-frame skipping of exon 9 in cystic fibrosis transmembrane conductance regulator (CFTR) mRNA transcripts (exon 9-) occurs in the respiratory epithelium. To explore the genetic basis of this event, we evaluated respiratory epithelial cells and blood leukocytes from 124 individuals (38 with cystic fibrosis (CF), 86 without CF). We found an inverse relationship between the length of the polythymidine tract at the exon 9 splice branch/acceptor site and the proportion of exon 9- CFTR mRNA transcripts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
323
4
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 461 publications
(341 citation statements)
references
References 49 publications
12
323
4
2
Order By: Relevance
“…23 This nonfunctional CFTR mRNA accounts for up to 92% of the total mRNA when the 5T allele is found on both CFTR genes. 11 We observed a significant proportion of Chinese CBAVD males who have the 5T allele (44.50%), as compared with the control males (13.46%). Also, a high frequency of homozygous (5T/5T) was found in the Chinese CBAVD patients ( Table 1).…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 63%
See 2 more Smart Citations
“…23 This nonfunctional CFTR mRNA accounts for up to 92% of the total mRNA when the 5T allele is found on both CFTR genes. 11 We observed a significant proportion of Chinese CBAVD males who have the 5T allele (44.50%), as compared with the control males (13.46%). Also, a high frequency of homozygous (5T/5T) was found in the Chinese CBAVD patients ( Table 1).…”
Section: Cftr Polymorphisms In Chinese Males With Cbavd Wh Ni Et Al 688mentioning
confidence: 63%
“…10 The 7T or 9T allele generate a predominantly normal mRNA transcript, whereas the 5T variant affects splicing efficiency and results in reduced levels of normal mRNA due to deletion of exon 9. 11 The protein product of the CFTR transcript lacking exon 9 is devoid of cyclic adenosine monophosphate-activated chloride conductance, and therefore, the 5T allele is now considered as a mild mutation with an incomplete penetrance. 11,12 Prior studies have demonstrated that the disease penetrance of 5T depends on the copy number of its adjacent TG repeats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The IVS-8 polymorphism affects the splicing efficiency of intron 8. 17,18 A tract of 7T or 9T at the 3Ј end of intron 8 insures proper splicing of the intron while a 5T results in a majority of mRNA lacking exon 9. 19 -22 Each mutation is independently considered mild because in both cases, residual activity of the ion channel remains.…”
mentioning
confidence: 99%
“…The probability of alternative splicing of exon 9 is related to the genotype of poly T and TG repeats in intron 8. 20 The analysis of transcripts is not routinely performed to detect the CFTR mutations in medical genetic laboratories, but a recent study identified a novel insertion between exons 10 and 11. 21 Another study of CF patients with only one mutation in the coding region of CFTR demonstrated a pathological reduction in the amount of RNA from the other allele in 5 of 11 patients.…”
Section: Discussionmentioning
confidence: 99%